A screening technique for resistance to Fusarium root for of common bean - Mukankusi, Clare Mugisha; Melis, R; Derera, J.; Buruchara, Robin Arani; Mark, D. (2011)
Resistance to Fusarium root rot (FRR) in common bean is documented as a quantitative trait and as such is greatly influenced by several environmental factors. A reproducible disease screening technique that considers the selection environment is therefore important in selecting resistant lines. A study was conducted to evaluate soil composition and irrigation frequency on the severity of FRR, using a predominant pathogenic isolate from SW Uganda at the International Centre for Tropical Agriculture (CIAT) in Uganda. Five soil compositions (i) 80% lake sand:20% forest soil, ii) 50% lake sand:50% forest soil, iii) 80% swamp soil:20% forest soil, iv) 50% swamp soil:50% forest soil and v) forest soil alone), and five irrigation frequency levels (once a week, twice a week, three times a week, four times a week, and daily) were evaluated on six common bean varieties with varying levels of resistance to FRR. Forest soil and 50% swamp soil: 50% forest soil (soil composition); daily irrigation and irrigation once a week (irrigation frequency) differentiated test varieties most distinctly, according to their reaction to FRR. In conclusion, a combination of forest soil and daily watering using a pathogenic isolate FSP-3 provided adequate FRR disease levels for disease evaluation and differentiation of bean varieties and was adopted for genetic studies on FRR resistance in beans.